The Combined Effect of Cold and Copper Stresses on the Proliferation and Transcriptional Response of Listeria monocytogenes - Quesille-Villalobos, Ana María; Parra, Angel; Maza, Felipe; Navarrete, Paola; González, Mauricio; Latorre, Mauricio; Toro, Magaly; Reyes-Jara, Angélica (Frontiers in Microbiology, 2019)
Listeria monocytogenes is a foodborne pathogen that can cause severe disease in susceptible humans. This microorganism has the ability to adapt to hostile environmental conditions such as the low temperatures used by the food industry for controlling microorganisms. Bacteria are able to adjust their transcriptional response to adapt to stressful conditions in order to maintain cell homeostasis. Understanding the transcriptional response of L. monocytogenes to stressing conditions could be relevant to develop new strategies to control the pathogen. A possible alternative for controlling microorganisms in the food industry could be to use copper as an antimicrobial agent. The present study characterized three L. monocytogenes strains (List2-2, Apa13-2, and Al152-2A) adapted to low temperature and challenged with different copper concentrations. Similar MIC-Cu values were observed among studied strains, but growth kinetic parameters revealed that strain List2-2 was the least affected by the presence of copper at 8 ºC. This strain was selected for a global transcriptional response study after a 1 hour exposition to 0.5 mM of CuSO4x5H2O at 8 ºC and 37 ºC. The results showed that L. monocytogenes apparently decreases its metabolism in response to copper, and this reduction is greater at 8 ºC than at 37 °C. The most affected metabolic pathways were carbohydrates, lipids and nucleotides synthesis. Finally, 15 genes were selected to evaluate the conservation of the transcriptional response in the other two strains. Results indicated that only genes related to copper homeostasis showed a high degree of conservation between the strains studied, suggesting that a low number of genes is implicated in the response to copper stress in L. monocytogenes. These results contribute to the understanding of the molecular mechanisms used by bacteria to overcome a combination of stresses. We concluded that the application of copper in low concentrations in cold environments may help to control foodborne pathogens as L. monocytogenes in the industry.